State and the Violence Monopoly: public security plans in Brazil (Research, Society and Development, 2020)
The exposed work aims to collaborate for the discussion of public security in Brazil, considering the need for state leadership to guarantee a safe life for its population. The aligned objective was to demonstrate the leading role of the State in the attribute of the monopoly of violence for the repression of crime in society. The qualitative methodology was the choice used in the research, consulting bibliographical and documentary sources. The result undermines the inefficiency of national plans to legitimize the state's monopoly in guaranteeing security. By way of conclusion, it demonstrates insipient advances made by Brazilian public security plans and the absence of social public policies that corroborate a safe society.